Analiza stateczności cienkościennych dźwigarów skrzynkowych obciążonych cieplnie - Kubiak, T.; Niezgodziński, T. (Katedra Wytrzymałości Materiałów i Konstrukcji, Politechnika Łódzka, 2003)
W pracy zaprezentowano rozważania dotyczące słuszności przyjmowania założenia prostych brzegów podczas analizy stateczności płyt obciążonych termicznie. Przedstawiono wyniki obliczeń numerycznych (MES) dla dźwigarów oraz płyt jako model blach środnika pomiędzy żebrami i przeponami, obciążonych termicznie - napawanie nakładek w procesie prostowania technologicznego [ l]. Analizę MES przeprowadzono przy pomocy profesjonalnego pakietu ANSYS.

In this paper the correctness of straight edge foundation in stability analysis of thin-walled structures has been considered. Results of numerical calculation for plate and girders subjected to therrnal load have been presented. The applied therrnal load was the same as in technologi cal pre-stressing process [ 1] which consists in welding metal straps to the box-girder, parallel to the beam axis. To perfonn the computation of the stress distribution of webs, the finite element method (ANSYS software package) is applied.
Stability of thin-walled girders subjected to thermal load
Keywords: stateczność; płyty obciążone termicznie; cienkościenne dźwigary skrzynkowe; stability; thermally loaded plates; thin-walled box girders